PENAMBAHAN KEWENANGAN CONSTITUTIONAL QUESTION KEPADA MAHKAMAH KONSTITUSI REPUBLIK INDONESIA UNTUK MENJAMIN HAK-HAK KONSTITUSIONAL WARGA NEGARA - Yossita Nora Sima Purba, - (2019)
Two decades Indonesia has declared it self to reform state administration for the implementation to be more democratic state. One form of legal reform in judicial power institutions is the idea of adopting a constitutional question mechanism into the Indonesian justice system. Constitutional question refers to a mechanism for testing the constitutionality of the law, namely in the case of a judge who is adjudicating a case in doubt about the constitutionality of the law that applies to the case. this thesis would like to examine about the urgency of applying constitutional question and how can the Constitutional Court use the authority of constitutional question in Indonesia. Research method used is normative juridical writing from library materials. the research results found the urgency for the implementation of constitutional question in Indonesia. With the existence of such mechanism, court decisions that are contrary to the constitution and violate the constitutional rights of the citizens can be avoided; the testing material of the legislation becomes expansive; and unnecessary constitutional rights violations can be avoided. If applied in Indonesia, the basis of the authority of constitutional question may be regulated through constitutional amendment, the revision of the Constitutional Court Law, the Constitutional Court Decision, or the extension of legal standing of state institutions as one of the applicants for constitutional review.